Australia lacks stem succulents but is it depauperate in plants with crassulacean acid metabolism (CAM)?. (June 2016) - Holtum, Joseph AM; Hancock, Lillian P; Edwards, Erika J; Crisp, Michael D; Crayn, Darren M; Sage, Rowan; Winter, Klaus
Highlights: The first census of CAM in a continental flora. Australia is CAM depauperate. The incidence of CAM is 20% of the planetary average. Facultative CAM appears common in terrestrial species. Strong CAM is rare in terrestrial species and more common in epiphytes. The Australian continent is poorly sampled for CAM. Abstract : In the flora of Australia, the driest vegetated continent, crassulacean acid metabolism (CAM), the most water-use efficient form of photosynthesis, is documented in only 0.6% of native species. Most are epiphytes and only seven terrestrial. However, much of Australia is unsurveyed, and carbon isotope signature, commonly used to assess photosynthetic pathway diversity, does not distinguish between plants with low-levels of CAM and C3 plants. We provide the first census of CAM for the Australian flora and suggest that the real frequency of CAM in the flora is double that currently known, with the number of terrestrial CAM species probably 10-fold greater. Still unresolved is the question why the large stem-succulent life — form is absent from the native Australian flora even though exotic large cacti have successfully invaded and established in Australia.